# Prove the followi

LHS = sin6x + cos6x

= (sin2x)3 + (cos2x)3

We know that a3 + b3 = (a + b) (a2 + b2 – ab)

= (sin2x + cos2x) [(sin2x)2 + (cos2x)2 – sin2x cos2x]

We know that sin2x + cos2x = 1 and a2 + b2 = (a + b)2 – 2ab

= 1 × [(sin2x + cos2x)2 – 2sin2x cos2x – sin2x cos2x

= 12 - 3sin2x cos2x

= 1 - 3sin2x cos2x = RHS

Hence proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Find the values oRD Sharma - Mathematics

Prove that :
<
RD Sharma - Mathematics

The value of sin Mathematics - Exemplar

The value of <spaMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

If 12 sin x – 9 sRD Sharma - Mathematics

Write the intervaRD Sharma - Mathematics